Improving Young Learners’ Speaking Skills with Picture Description Technique - Jaolath, Maria; Binnendyk, Sophia; Rijoly, Helena M. A. (MATAI: International Journal of Language Education, 2024)
This study aims to determine how Describing Picture Technique improves students’ speaking skills. The data collected from the students at SD Negeri 1 Latihan SPG Ambon, grade Va. Exploratory sequential design is used as the method in this study, whereas the qualitative data were collected using an observation checklist to observe how this technique was implemented, and the students’ response. The teacher wrote a reflective journal to reflect each teaching and learning process. An in-depth interview was done to know the teacher’s opinion on using DPT to improve students’ speaking skills and the challenges in implementing this technique. The quantitative data, which are pre-test and post-test, were conducted to confirm the result of the qualitative data. The findings showed that DPT can improve young learners’ speaking skills. Furthermore, this technique increased the students’ vocabulary, improved pronunciation, and made them more comfortable speaking. However, there were still challenges found in implementing DPT faced by the teacher. Hence, these findings offer insights to the teachers to use a suitable teaching technique to improve young learners' speaking skills and what they need to prepare before implementing this technique.